Exploring women's preferences for birth settings in England: A discrete choice experiment. - Benjamin Rupert Fletcher; Rachel Rowe; Jennifer Hollowell; Miranda Scanlon; Lisa Hinton; Oliver Rivero-Arias (PLoS ONE, 2019)
Objective To explore pregnant women's preferences for birth setting in England. Design Labelled discrete choice experiment (DCE). Setting Online survey. Sample Pregnant women recruited through social media and an online panel. Methods We developed a DCE to assess women's preferences for four hypothetical birth settings based on seven attributes: reputation, continuity of care, distance from home, time to see a doctor, partner able to stay overnight, chance of straightforward birth and safety for baby. We used a mixed logit model, with setting modelled as an alternative-specific constant, and conducted a scenario analysis to evaluate the impact of changes in attribute levels on uptake of birth settings. Main outcome measures Women's preferences for birth setting. Results 257 pregnant women completed the DCE. All birth setting attributes, except 'time to see doctor', were significant in women's choice (p<0.05). There was significant heterogeneity in preferences for some attributes. Changes to levels for 'safety for the baby' and 'partner able to stay overnight' were associated with larger changes from baseline uptake of birth setting. If the preferences identified were translated into the real-world context up to a third of those who reported planning birth in an obstetric unit might choose a midwifery unit assuming universal access to all settings, and knowledge of the differences between settings. Conclusions We found that 'safety for the baby', 'chance of a straightforward birth' and 'can the woman's partner stay overnight following birth' were particularly important in women's preferences for hypothetical birth setting. If all birth settings were available to women and they were aware of the differences between them, it is likely that more low risk women who currently plan birth in OUs might choose a midwifery unit.